Relevansi Penerapan ‘Iddah di Era Teknologi Modern - Nurnazli, Nurnazli (Universitas Islam Negeri Raden Intan Lampung, 2017)
The development of science and technology today is not a reason to remove the provisions about ‘iddah that has been set in the Qur'an and Sunnah. 'Illat law and the purpose of enactment of ‘iddah which has been discussed needs to be reviewed. ‘iddah not only to know the empty uterus of the fetus, self-introspection, condition and period of mourning, but there is a higher purpose, that is belief in Allah and honor the noble covenant at the marriage ceremony. The noble agreement is realized in the ijâb and qabûl between men and women guardians. Consequently, if the marriage breaks up either because of death or divorce, both sides must respect the agreement. They must be equally restricted with the ‘iddah way until the time set by Syar'i, especially for women whose existence is more glorified and also the aim of the law' ‘iddah is for the common good.